Methylmercury photodemethylation is inhibited in lakes with high dissolved organic matter. (January 2018) - Klapstein, Sara J.; Ziegler, Susan E.; O'Driscoll, Nelson J.
Abstract: Photodemethylation can be one of the primary processes for loss of neurotoxic methylmercury (MeHg) in freshwater lakes. Few studies have quantified seasonal variations in photodemethylation rate constants as a function of dissolved organic matter (DOM). We conducted 1-week irradiation experiments in two seasons to test for spatial and temporal differences in photodemethylation potential in temperate lake waters. Six study lakes in Kejimkujik National Park, Nova Scotia were sampled in summer and fall to include a range of naturally occurring DOM concentrations (4.4–13.4 and 3.9–16.4 mg C L −1, respectively). A negative linear relationship (R 2 = 0.76, p = 0.01) was found between DOM concentration and photodemethylation rate constant across seasons, indicating that DOM is a strong predictor of MeHg photodemethylation independent of seasonal effects. The two highest carbon lakes (BDW and PEB) had significantly higher energy-normalized photodemethylation rate constants in summer compared to fall corresponding with lower DOM concentrations in summer relative to fall. Additionally, there were negative linear relationships between MeHg photodemethylation and DOM photomineralization (R 2 s = 0.58–0.72) and DOM photobleaching (R 2 s = 0.83–0.90). This key finding suggests that competition for photons within DOM structures may reduce the potential for MeHg photodemethylation in high carbon waters and that this relationship persists across seasons. Graphical abstract: Highlights: Highlights – Klapstein et al. Environmental Pollution. No direct seasonal effect on photodemethylation rate constants across lakes. Photodemethylation rate constants lower in higher dissolved organic matter waters. Significant tradeoff between DOM phototransformations and MeHg photodemethylation. Abstract : Less photodemethylation of MeHg occurs in freshwaters with high DOM due to a tradeoff between DOM structures that are involved in photoreactions.